2012
DOI: 10.1016/j.medengphy.2011.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the accuracy of MRI generated 3D models of long bones compared to CT generated 3D models

Abstract: Orthopaedic fracture fixation implants are increasingly being designed using accurate 3D models of long bones based on computer tomography (CT). Unlike CT, magnetic resonance imaging (MRI) does not involve ionising radiation and is therefore a desirable alternative to CT. This study aims to quantify the accuracy of MRI-based 3D models compared to CT-based 3D models of long bones. The femora of five intact cadaver ovine limbs were scanned using a 1.5 T MRI and a CT scanner. Image segmentation of CT and MRI data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 31 publications
4
92
0
2
Order By: Relevance
“…The obtained bone model was based on the contour of the bone marrow, because the cortical bone is not visible on the MRI. Rathnayaka et al (2012) determined that long bone models obtained from MRI-based data did not differ statistically from those obtained with CT.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The obtained bone model was based on the contour of the bone marrow, because the cortical bone is not visible on the MRI. Rathnayaka et al (2012) determined that long bone models obtained from MRI-based data did not differ statistically from those obtained with CT.…”
Section: Discussionmentioning
confidence: 96%
“…All manual adjustments must be performed by a person capable of verifying the segmentation area to minimise the loss of digital image integrity and to avoid minor discontinuities during segmentation. In order to obtain a 3D model with a high geometric accuracy, the person performing the modelling should be familiar with anatomy in order that errors in bone boundary determination are kept to a minimum (Lee et al 2008;Anastasi et al 2009;Rathnayaka et al 2012). Similar observations were made during segmentation of CT data (Rathnayaka et al 2010;Rathnayaka et al 2012).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rathnayaka et al (17) and Lee et al (18) have used 3D bone models reconstructed from CT and MRI images to then quantified their surface differences. They reported that the mean errors between the CT and MRI models were as low as 0.23 and 0.5 mm for the human and ovine femora, respectively (17,18). These results suggested that MRI models can be reconstructed with good accuracy as compared to the CT models.…”
Section: Original Articlementioning
confidence: 98%